2020
DOI: 10.1111/jbg.12513
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐genome resequencing reveals loci under selection during silkworm improvement

Abstract: Breeding or genetic improvement refers to the process of artificial selection following domestication; as such, it has had a major influence on modern agriculture and animal production. Improvement generally focuses on traits that greatly affect the economic performance. Therefore, understanding the genetic basis underlying improvement will contribute to the identification of genes controlling economic traits and will facilitate future crop and animal breeding. However, genome-wide study of the molecular basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Therefore, multi‐omics research combined with silk gland weight studies is essential (Zhang et al, 2023). Proteomics analysis has demonstrated that the posterior silk gland with high yield has higher expression of genes associated with ribosome pathways and, therefore, may have higher translational ability (Li et al, 2021). The posterior silk gland with low‐yield silkworms is characterised by a slower protein translation rate, a lower energy utilisation rate and greater protein breakdown than that of high‐yield silkworms (Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, multi‐omics research combined with silk gland weight studies is essential (Zhang et al, 2023). Proteomics analysis has demonstrated that the posterior silk gland with high yield has higher expression of genes associated with ribosome pathways and, therefore, may have higher translational ability (Li et al, 2021). The posterior silk gland with low‐yield silkworms is characterised by a slower protein translation rate, a lower energy utilisation rate and greater protein breakdown than that of high‐yield silkworms (Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%